Characterization of crude oils derived from carbonate and siliciclastic source rocks using FTICR-MS. (September 2021) - Hosseini, S. Hossein; Sachsenhofer, Reinhard F.; Snowdon, Lloyd R.; Oldenburg, Thomas B.P.
Highlights: Oils from carbonate and siliciclastic rocks can be distinguished by composition. The differences are more pronounced in the O1, N1 S1, S1 and HC species. Two novel source-related proxies based on FTICR–MS data are identified. Published FTICR–MS data were used to verify the robustness of the proposed proxies. Abstract: The scope of this study was to develop robust lithofacies proxies which are less affected by other geochemical processes such as maturity and biodegradation. Here, crude oils derived from carbonate and siliciclastic source rocks from different petroleum settings were investigated using Fourier transform ion cyclotron resonance mass spectrometry (FTICR-MS), thereby providing information on the role of depositional environment in controlling the chemical composition of hydrocarbons. The carbonate oils belong to the Western Canada Sedimentary Basin (WCSB) and the siliciclastic oils were mainly collected from the Austrian parts of the Molasse Basin and the Vienna Basin, Austria. The variations in chemical composition, aromaticity as well as alkylation degree of the main compound classes in both oil types are discussed in detail using data from FTICR-MS in two different ionization modes: electrospray ionization in negative ion mode (ESI–N) and atmospheric pressure photoionization in positive ion mode (APPI–P). The results obtained from both ionization modes indicate that the chemical compound distributions of acidic constituents such as oxygen-only components (the O1 to O4 classes) and the N1 S1 class, as well as sulfur and hydrocarbon species in oils from carbonates are clearly different from those generated by siliciclastic rocks. Most likely, the observed differences are attributed to depositional environments of the respective source rocks as the impacts of other processes such as thermal maturity and biodegradation, were mitigated by selection of non-biodegraded oils that display comparable maturation levels. The calculated vitrinite reflectance (%R c ) in most of the selected oils range between 0.5 and 0.8. The observed differences in chemical composition of oils from carbonates and siliciclastics lead to suggested novel source-sensitive proxies based on the DBE distribution of the S1 and HC species (from APPI–P) and the O1 and N1 S1 classes (from ESI–N). The former proxy is the ratio of the S1 class DBE 9 group (radical ions; likely sum of alkylated dibenzothiophenes) relative to the HC class DBE 10 group (radical ions; likely sum of alkylated phenanthrenes). It appears that this proxy is mirroring the "DBT/P ratio" obtained from GC–MS data over a much broader range of molecular masses up to approximately 1000 Da. The other proxy is based on the observed differences between the O1 class DBE 4 group and the N1 S1 class DBE 14 group. Whereas oils derived from the siliciclastic source rocks show higher concentrations of the O1 class, oils originated from the carbonate source units are enriched in the N1 S1 species. Finally, published FTICR-MS data (APPI–P) from both oil source types with varying levels of maturation and biodegradation are included, in order to verify the robustness of the proposed proxies.